A call to arms: time to do cognitive science in Latin America - Fernando Marmolejo-Ramos (Universidad de San Buenaventura, 2008)
Previous theoretical reviews about the development of Psychology in Latin America suggest that Latin American psychology has a promising future. This paper empirically checks whether that status remains justified. In so doing, the frequency of programs/research domains in three salient psychological areas is assessed in Latin America and in two other regions of the world. A chi-square statistic is used to analyse the collected data. Programs/research domains and regions of the world are the independent variables and frequency of programs/research domains per world region is the dependent variable. Results suggest that whereas in Latin America the work on Social/Organizational Psychology is moving within expected parameters, there is a rather strong focus on Clinical/Psychoanalytical Psychology. Results also show that Experimental/Cognitive Psychology is much underestimated. In Asia, however, the focus on all areas of psychology seems to be distributed within expected parameters, whereas Europe outperforms regarding Experimental/Cognitive Psychology research. Potential reasons that contribute to Latin Americas situation are discussed and specific solutions are proposed. It is concluded that the scope of Experimental/Cognitive Psychology in Latin America should be broadened into a Cognitive Science research program.